Diagnostics of subject results on literary reading in a primary school as a tool of education quality control - Vlasova V. M. (Upbringing and education: theory, metodology and practice, 2016)
the following article reveals a technology of pedagogical diagnostics of subject results as a basis of educational monitoring, in other words, it is the tool, more concrete fast studying, assesment, regulating and correction of the process or event, permitting the teacher with smaller losses to achieve more significant results, higher quality of literary education.
Keywords: универсальные учебные действия; качество образования; предметные результаты; диагностика; Universal educational actions; педагогический мониторинг; quality of education; коррекционно-развивающая деятельность; читательские умения; читательский кругозор; дифференцированно-развивающая работа; технологические карты; subject results; diagnostics; teacher's monitoring; correcting and developing activity; reader's skills; reader's outlook; differentiated developing work; technological cards